The characterization of NMR signal for blood pressure monitoring system and its testing - Bambang Murdaka Eka Jati; . Kusminarto; Agung Bambang Setio Utomo; Bambang Irawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACT A blood monitoring system based on NMR method has been designed on constructed. This set-up of equipment used magnetic permanent, radio frequency (RF), receiver coil (RC), function generator (FG), amplifier which included the filter, as well as the oscilloscope digital storage. The background of this research was based on the sensitivity of NMR signal. The signal must be separated from signals background. This method was done by adjusting the frequency on FG, which was connected to radio frequency (RF) coil, on empty sample. Subsequently, NMR signal was received by RC, and that signal could be shown on oscilloscope at resonance condition. The true frequency on NMR signal was Larmor frequency, and the other was background. The two variables of this experiment were the position of RF coil and the location temperature (20 up to 30oC). In conclusion, the resonance frequency of NMR signal (as Larmor frequency) was 4.7 MHz (at static magnetic field of 1,600 gauss) and it could be separated from background signals (3.4 and 6.2 MHz), and that signal was almost constant to room temperature. The equipment was used for sample testing. It gave systole/diastole data of 110/70 mmHg (on sphygmomanometer) that was similar to 17/9 mV (on NMR signal). ABSTRAK Telah dikembangkan alat pemantauan tekanan darah berdasar prinsip NMR.